GPS-based system for distributed device synchronization - Meyer, F.; Bahr, A.; Lochmatter, T. (Book of Abstracts. 5th International Congress on Science and Skiing, Dec. 14 - 19, 2010, St. Christoph am Arlberg, 2010)
INTRODUCTION: The aim of this project was to develop an embedded System which allows for the synchronization of multiple recording devices. In our case the recording devices consist of multiple cameras and a data recorder. As the cameras are spread over a wide area and the data recorder is attached to a skier, it is essential that all devices are synchronized wirelessly and that the system is robust enough for the outdoor environment. The method which is commonly used for synchronization records a jump at the beginning of the run, to have a peak signal recorded on the different devices (camera, force plate, insole pressure measurements or accelerometers). The synchronization is then recovered manually with low accuracy (about one Video frame: 0.02 s). Other available multi-camera systems are either synchronized by using cables to connect all cameras to the same trigger signal, or the unsynchronized video streams are aligned in post processing (Pourcelot, 2000).